Description of two females of Leptagrion Selys (Odonata: Coenagrionidae) - Furieri, Karina S.; Fraga, Felipe B.; Tribull, Carly; Colombo, Wesley D. (Zootaxa, 2020)
In this paper, we provide taxonomic updates on the genus Leptagrion Selys: the females of L. acutum Santos and L. porrectum Selys are illustrated and diagnosed for the first time. We also add to the original description of L. acutum based on a male collected in the Atlantic Forest. A key for females is also provided for the currently known species of Southeast of Brazil.